IMPC-based screening revealed that ROBO1 can regulate osteoporosis by inhibiting osteogenic differentiation - Zhang, Xiangzheng; Wang, Yike; Zheng, Miao; Wei, Qi; Zhang, Ruizhi; Zhu, Keyu; Zhai, Qiaocheng; Xu, Youjia (Frontiers in Cell and Developmental Biology, 2024)
The utilization of denosumab in treating osteoporosis highlights promising prospects for osteoporosis intervention guided by gene targets. While omics-based research into osteoporosis pathogenesis yields a plethora of potential gene targets for clinical transformation, identifying effective gene targets has posed challenges. This study addresses this issue by integrating clinical osteoporosisrelated omics data and leveraging the International Mouse Phenotyping Consortium (IMPC) database. Through this approach, we've developed a method for accurately identifying gene targets capable of directly regulating osteogenic differentiation. We also verified the function of ROBO1 in Saos-2, 3T3-E1 and bone marrow mesenchymal stem cells (BMSCs), and found that the weakened osteogenic differentiation function in 3T3-E1 caused by downregulation of Robo1 may be related to the activation of inflammation signaling pathways. Our study provides a new regulatory molecular target for the pathogenesis of osteoporosis, which is expected to provide new solutions for the osteoporosis intervention.